FEATURES OF WORLD RANKINGS OF UNIVERSITIES - Mukumova Nargis Nuriddinovna; Saidirasulov Alisher Zokirovich; Rayimov Marufjon Abdurashid ogli (Scholar Express Journals, 2022)
An important component of the modern world market of educational services is the compilation of global university rankings. This article presents the methodology of the Big Three international rankings, in particular, the criteria of QS World University Rankings, Times Higher Education World University and Webometrics are considered
Keywords: Ranking; universities; global university rankings; THE